Pengelolaan Arsip Digital Pada Bagian Organisasi Sekretariat Daerah Kabupaten Tuban - Setiorini, Setiorini; Aulianto, Dwi Ridho (Universitas Negeri Padang, 2024)
Archives are an important source of information that must be well-managed to enable quick retrieval when needed. Archive management can positively impact an organization's reputation and hinder the achievement of its goals. With technological developments, archives are not only stored physically but also in digital form. This study aims to analyze the digital archive management practices of the Organization Division of the Regional Secretariat of Tuban Regency. The research method used is a qualitative approach with data collection techniques through observation and interviews. The research findings show that the main purpose of digital archive management in the Organization Division of the Regional Secretariat of Tuban Regency is to facilitate and accelerate the retrieval of archives when needed. However, digital archive management faces several obstacles, mainly the need for more education and training for employees in managing archives. To overcome these obstacles, the agency has made efforts to provide mentoring programs for employees to manage archives properly and correctly